Meningkatkan Motivasi Belajar dan Hasil Belajar Tematik Siswa Kelas Lima melalui Model Quantum Teaching - Haffit Mufarrid; Yalvema Miaz; Syafri Ahmad; Irsyad Irsyad (CV. AFDIFAL MAJU BERKAH, 2023)
Based on a preliminary study conducted in class V of UPT SDN 04 Siparayo, it was observed that teachers were not optimizing the use of learning models, which resulted in a decrease in students' learning motivation and low learning outcomes. Teachers tended to still use conventional learning models. This study aims to determine the effect of using the Quantum Teaching model on students' motivation and learning outcomes. The steps of the Quantum Teaching model are: (1) grow, (2) experience, (3) name, (4) demonstrate, (5) repeat, and (6) celebrate. Students experience enjoyable learning and find it easier to understand the subject matter. This study is an experimental study with a quasi-experiment design in the form of a pretest-Post-test non-equivalent group design. Data were obtained from quantitative research results. The results showed that the level of learning motivation of students taught with the Quantum Teaching model was higher compared to students taught with conventional learning. Furthermore, for learning outcomes, students taught with Quantum Teaching model obtained higher average scores compared to students taught with conventional learning. To see the effect of the Quantum Teaching model on students' motivation and learning outcomes, a One-Way ANOVA test was conducted, which obtained a higher F-value compared to the F-table, is an F value of 4.098 is greater than the tables F value of 3.555 at a significance level of 0.05 This indicates that there is an influence of using the Quantum Teaching model on students' learning motivation and outcomes. The application of the Quantum Teaching model in learning has a positive impact on students' motivation and learning outcomes. When learning using the Quantum Teaching model, students are seen to be motivated to participate in learning and their learning outcomes also improve. Therefore, the use of the Quantum Teaching model has a significant effect on students' motivation and learning outcomes.